Sublethal irradiation promotes the metastatic potential of hepatocellular carcinoma cells. Issue 1 (29th November 2020) - Cao, Yulin; Yin, Yuan; Wang, Xue; Wu, Zhifeng; Liu, Yuhang; Zhang, Fuzheng; Lin, Junhua; Huang, Zhaohui; Zhou, Leyuan
Abstract: Radiotherapy (RT) represents one of the major treatment methods for cancers. However, many studies have observed that in descendant surviving tumor cells, sublethal irradiation can promote metastatic ability, which is closely related to the tumor microenvironment. We therefore investigated the functions and mechanisms of sublethal irradiated liver nonparenchymal cells (NPCs) in hepatocellular carcinoma (HCC). In this study, primary rat NPCs and McA‐RH7777 hepatoma cells were irradiated with 6 Gy X‐ray. Conditioned media (CM) from nonirradiated (SnonR), irradiated (SR), or irradiated plus radiosensitizer celecoxib‐treated (S[R + D]) NPCs were collected and added to sublethal irradiated McA‐RH7777 cells. We showed that CM from sublethal irradiated NPCs significantly promoted the migration and invasion ability of sublethal irradiated McA‐RH7777 cells, which was reversed by celecoxib. The differentially expressed genes in differently treated McA‐RH7777 cells were enriched mostly in the AMP‐activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) signaling pathway. SR increased the migration and invasion ability of HCC cells by inhibiting AMPK/mTOR signaling, which was enhanced by the AMPK inhibitor compound C and blocked by the AMPK activator GSK‐621. Analyses of HCC tissues after neoadjuvant radiotherapy confirmed the effects of radiation on the AMPK/mTOR pathway. Cytokine antibody arrays and further functional investigations showed that matrix metalloproteinase‐8 (MMP‐8) partly mediates the promotion effects of SR on the migration and invasion ability of HCC cells by regulating AMPK/mTOR signaling. In summary, our data indicate that MMP‐8 secreted by irradiated NPCs enhanced the migration and invasion of HCC by regulating AMPK/mTOR signaling, revealing a novel mechanism mediating sublethal irradiation–induced HCC metastasis at the level of the tumor microenvironment. Abstract : In this work, we observed that conditioned media from sublethally irradiated liver nonparenchymal cells (NPCs) promoted the migration and invasion ability of sublethally irradiated McA‐RH7777 hepatoma cells. Further mechanistic studies revealed that matrix metalloproteinase‐8 (MMP‐8) secreted by NPCs enhanced the migration and invasion of hepatocellular carcinoma (HCC) by regulating the AMPK/mTOR signaling pathway. These findings might offer a new strategy for improving the therapeutic effect of radiotherapy.